2015
DOI: 10.4236/as.2015.64041
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Forage Mixing Rates and Organic Fertilizers on the Yield and Nutritive Value of Berseem Clover (<i>Trifolium alexandrinum</i> L.) and Annual Ryegrass (<i>Lolium multiflorum</i> Lam.)

Abstract: Berseem clover (Trifolium alexandrinum L.) is the main winter forage legume in Egypt. Despite that the yield and protein content of berseem clover are high, it is characterized by low dry matter content especially in the 1 st cut. Intercropping berseem clover with forage grasses, especially annual ryegrass (Lolium multiflorum Lam.) is a recommended technique to produce higher forage yield with better balanced nutritional quality. However, little is known about the performance of these proposed mixtures under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…The achieved results confirm that mixing forage grasses with EC improves the 1st cut DM content compared to the pure EC stands. Similar results were reported for clover-barley and clover-triticale mixtures (El-Karamany et al, 2012, 2014, also for clover-ryegrass mixtures grown under the organic farming conditions (Salama, 2015).…”
Section: Effectsupporting
confidence: 85%
“…The achieved results confirm that mixing forage grasses with EC improves the 1st cut DM content compared to the pure EC stands. Similar results were reported for clover-barley and clover-triticale mixtures (El-Karamany et al, 2012, 2014, also for clover-ryegrass mixtures grown under the organic farming conditions (Salama, 2015).…”
Section: Effectsupporting
confidence: 85%
“…Cereals yield more than clover monocultures and cereal-clover binary mixtures prior to Cut-1 (Contreras- Govea and Albrecht, 2005;Ross et al, 2005a;Shoaib et al, 2013;Andrzejewska et al, 2014), yet some researchers found that mixtures yields equal or greater DM yield than component sole corps (Vasilakoglou and Dhima, 2008;Salama, 2015).…”
Section: Dry Matter Productionmentioning
confidence: 99%
“…Egyptian clover is a high-quality leguminous crop for winter forage (Muhammad et al, 2014). Egyptian clover is involved in rotation with non-leguminous crops to increase crop productivity (Salama, 2015).…”
Section: Introductionmentioning
confidence: 99%